Load frequency control in Island micro-grid with electric vehicles and renewable energy sources using modified fractional order PID controller - Tola, Omokhafe James; Irefu, Ovis Daniel; Ambafi, James Garba (Institute of Advanced Engineering and Science, 2024)
This paper presents a modified fractional-order proportional-integral-differential (MFOPID) controller for load frequency control in an Island microgrid based on an electric vehicle (EV) and renewable energy source. It tackles the intermittent energy sources and the dynamic of the load change with reduced speed and the quality of response generated on the microgrid. The MFOPID controller gains are well turned using a metaheuristic grasshopper optimization algorithm (GOA) technique to determine its robustness and optimal system performance. The controller gains are evaluated with three different searching agent populations. The proposed MFOPID with GOA improved system performance frequency by 19.485 Hz compared to 14.1151 Hz of the benchmark model. It takes 6.9068 s of the proposed model to settle compared to 16.6796 s of FOPID.